Cloning of the Cytochrome b Gene From the Tomato Powdery Mildew Fungus Leveillula taurica Reveals High Levels of Allelic Variation and Heteroplasmy for the G143A Mutation - Mosquera, Sandra; Chen, Li-Hung; Aegerter, Brenna; Miyao, Eugene; Salvucci, Anthony; Chang, Ti-Cheng; Epstein, Lynn; Stergiopoulos, Ioannis (Frontiers in Microbiology, 2019)
LLeveillula taurica is a major pathogen of tomato and several other crops that can cause substantial yield losses in favorable conditions for the fungus. Quinone outside inhibitor fungicides (QoIs) are routinely used for the control of the pathogen in tomato fields across California, but their recurrent use could lead to the emergence of resistance against these compounds. Here, we partially cloned the cytochrome b gene from L. taurica (Lt cytb) and searched within populations of the fungus collected from tomato fields across California for mutations that confer resistance to QoIs. A total of 21 single nucleotide polymorphisms (SNPs) were identified within a 704 bp fragment of the Lt cytb gene analyzed, of which five were non-synonymous substitutions. Among the most frequent SNPs encountered within field populations of the pathogen was the G143A substitution that confers high levels of resistance against QoIs in several fungi. The other four amino acid substitutions were novel mutations, whose effect on QoI resistance is currently unknown. Sequencing of the Lt cytb gene from individual single-cell conidia of the fungus further revealed that most SNPs, including the one leading to the G143A substitution, were present in a heteroplasmic state, indicating the co-existence of multiple mitotypes in single cells. Analysis of the field samples showed that G143A substitution is predominantly heteroplasmic also within populations of L. taurica in California, suggesting that QoI resistance in this fungus is likely to be quantitative rather than qualitative